Savage road : a thriller - Hauty, Chris (New York : Emily Bestler Books/Atria, 2021)
When a series of devastating cyber attacks rock the United States, Hayley Chill is with tracking down their source. NSA analysts insist that Moscow is the culprit, but that accusation brings plenty of complications to Hayley's primary operation directing a double agent against the Russians. With increasing pressure on the president to steer him towards a devastating war, it's up to Hayley to stop the mysterious computer hacker and prevent World War III-while also uncovering some shocking truths about her own life. -- adapted from jacket.
Sequel to: Deep state.
Keywords: United States. -- National Security Agency -- Fiction; United States. -- National Security Agency; Cyberterrorism -- Fiction; Hackers -- Fiction; Intelligence officers -- Fiction; National security -- Fiction; FICTION / Thrillers / Political; FICTION / Thrillers / Suspense; FICTION / Thrillers / Espionage; Cyberterrorism; Diplomatic relations; Hackers; Intelligence officers; National security; United States -- Foreign relations -- Russia -- Fiction; Russia; United States; Fiction; Novels; Political fiction; Thrillers (Fiction); Suspense fiction; Political fiction; Thrillers (Fiction); Novels